Analisis Faktor-Faktor yang Mempengaruhi Kualitas Laba dengan Kualitas Audit sebagai Variabel Intervening Perusahaan Sektor Konsumsi di BEI - Titin Krisnawati; Agung Budi Sulistyono; Siti Maria Wardayanti (Fakultas Ekonomi, UIN Maliki Malang, 2021)
Companies that have good profit quality can describe good company conditions. And an independent public accountant will provide good value to the company. The purpose of this research is to examine the quality of profits affected by liquidity, profitability, leverage, corporate growth, and audit quality in consumer goods industry sector companies in IDX. This study uses explanatory research based on hypothesis testing. The data used by secondary data and samples was selected using purposive sampling methods of 24 companies, with criteria covering listing companies in IDX for a minimum of three years, not performing corporate actions such as acquisitions or mergers during the observation period, having no negative return and total equity. The analysis used is descriptive, path analysis, and hypothesis test. The results showed liquidity, profitability, leverage, and growth of companies influenced the quality of profits through quality audits.